Enzymatic preparation of structured triacylglycerides containing γ-linolenic acid. (September 2020) - López-Martínez, J.E.; Romero, Rubi; Natividad, Reyna; Torres, Carlos F.; García, Hugo S.; Baeza-Jiménez, R.
Abstract: Structured triacylglycerides (STAG) rich in γ-linolenic acid (GLA) were prepared using a three-step process. First, with the addition of molecular sieves (MS) at different addition times (3, 9, 12 and 15 h) and loads (2.5, 5, 10 and 15%, based on the total weight of substrates), the enrichment of GLA from evening primrose oil (EPO) and 1-butanol (BtOH) was improved via Candida rugosa lipase-catalysed esterification reactions. Secondly, the GLA-enriched fraction was separated by thin-layer chromatography (TLC) to be further set to react during the third step in the presence of glycerol and Candida antarctica fraction B (CALB), under different enzyme loadings (5, 10, 15 and 20%, based on the total weight of substrates), temperatures (30, 40, 50 and 60 °C) and substrates molar ratios (1:1, 2:1, 3:1 and 4:1, GLA:glycerol). 60% of STAG containing 49 wt% of GLA were produced by using 15% of CALB at 60 °C and a 3:1 molar ratio. Highlights: Molecular sieves allowed an enrichment of GLA in esterification reactions. A 60% TAG content was achieved during glycerolysis reaction. The structured triacylglycerides produced contain 49% of GLA.